Determining the factors affecting intention of food waste recycling among household in Malaysia / Nur Syazana Mohd Saiful Bahari and Siti Aisyah Mohd Sharif - Mohd Saiful Bahari, Nur Syazana; Mohd Sharif, Siti Aisyah (2021)
Food waste has become a crucial issue for Malaysian authorities to manage. The lack of landfills to dispose of all of the food waste has prompted a lot of concern about how to handle the stack of food waste. Despite the fact that Malaysia has a high rate of food waste generation, over 90% of Malaysian food waste is biodegradable and recyclable. However, in order to prevent food waste, there is still a lack of information regarding food recycling especially among the society in Alor Setar area. The research aims to find out more about factors affecting the intention of food waste recycling in Malaysia. In addition, the study is focused to determine the intention, by considering four factors attitude, subjective norms, perceived behavioural control and the last factor is emotion. A total of 177 samples were collected, with each sample coming from residents of Alor Setar. The collected samples were put to the test to see how their intentions influenced all of the factors. All the samples, then are analysed by three types of analysis descriptive statistical technique, ANOVA test and Correlation analysis. Therefore, the research's findings answered the research questions by demonstrating a positive relationship between all of the factors and intention. Thus, the study will contribute to community goodwill, raise food waste recycling awareness, particularly among household food waste, and increase Malaysia's recycling rate.